A Script Analysis of Successful Police Interventions Involving Individuals in Crisis - Blais, Étienne (Canadian journal of criminology and criminal justice, 2023)
This study uses script analysis in criminology to identify steps and actions performed by police officers during their encounters with individuals in crisis to obtain their cooperation peacefully. Data were collected from 130 police reports. Descriptive and logistic regression analyses were respectively used to identify the main steps of police interventions and to estimate the effect of police actions on reactions from the person in crisis. A six-step script was identified: (1) receiving the emergency call; (2) arriving at the scene; (3) assessing the situation; (4) engaging with the person in crisis; (5) managing the situation; and (6) completing the intervention. During their interventions, officers use several techniques to obtain the cooperation of the person in crisis or de-escalate the crisis. Results indicate that support techniques (e.g., involving the person in finding a solution) lead to cooperation and permit effective de-escalation of the crisis. Conversely, individuals in crisis were less likely to cooperate or calm down when the police used nonphysical (e.g., using threats, disapproving of the person’s behavior) or physical control techniques (e.g., using constraint or intermediate weapons). Measures likely to improve police interventions with individuals in crisis are discussed, using the script analysis as a framework.